![image](https://tex.z-dn.net/?f=+%0A21x%5E2%2B39x-6%3C0%5C%5C%0A%5Cfrac%7B1%7D%7Bx%7D%2B%5Cfrac%7B1%7D%7Bx%2B1%7D%3E%3D%5Cfrac%7B1%7D%7Bx%2B2%7D%5C%5C%5C%5C%0A21x%5E2%2B39x-6%3D0%5C%5C+%0A7x%5E2%2B13x-2%3D0%5C%5C+%0AD%3D13%5E2-4%2A7%2A-2%3D225%5C%5C%0Ax%3D%5Cfrac%7B-13%2B15%7D%7B14%7D%3D%5Cfrac%7B1%7D%7B7%7D%5C%5C%0Ax%3D%5Cfrac%7B-13-15%7D%7B14%7D%3D-2+%0A%287x-1%29%28x%2B2%29%3C0%5C%5C++++++%0Ax+%5C+%5Cin+%5C+%28-2%3B%5Cfrac%7B1%7D%7B7%7D%29%5C%5C%5C%5C%0A%5Cfrac%7B1%7D%7Bx%7D%2B%5Cfrac%7B1%7D%7Bx%2B1%7D+%5Cgeq+%5Cfrac%7B1%7D%7Bx%2B2%7D%5C%5C%0A%5Cfrac%7B2x%2B1%7D%7Bx%28x%2B1%29%7D+%5Cgeq+%5Cfrac%7B1%7D%7Bx%2B2%7D%5C%5C+%0A%5Cfrac%7B%282x%2B1%29%28x%2B2%29%7D%7Bx%28x%2B1%29%28x%2B2%29%7D+%5Cgeq+%5Cfrac%7Bx%28x%2B1%29%7D%7Bx%28x%2B1%29%28x%2B2%29%7D%5C%5C%0A%282x%2B1%29%28x%2B2%29+%5Cgeq+x%28x%2B1%29%5C%5C+%0A2x%5E2%2B5x%2B2+%5Cgeq+x%5E2%2Bx%5C%5C%0Ax%5E2%2B4x%2B2+%5Cgeq+0%5C%5C%0AD%3D16-4%2A1%2A2%3D8%5C%5C%0Ax%3D%5Cfrac%7B-4%2B%5Csqrt%7B8%7D%7D%7B2%7D%3D-2%2B%5Csqrt%7B2%7D%5C%5C%0A)
=\frac{1}{x+2}\\\\
21x^2+39x-6=0\\
7x^2+13x-2=0\\
D=13^2-4*7*-2=225\\
x=\frac{-13+15}{14}=\frac{1}{7}\\
x=\frac{-13-15}{14}=-2
(7x-1)(x+2)<0\\
x \ \in \ (-2;\frac{1}{7})\\\\
\frac{1}{x}+\frac{1}{x+1} \geq \frac{1}{x+2}\\
\frac{2x+1}{x(x+1)} \geq \frac{1}{x+2}\\
\frac{(2x+1)(x+2)}{x(x+1)(x+2)} \geq \frac{x(x+1)}{x(x+1)(x+2)}\\
(2x+1)(x+2) \geq x(x+1)\\
2x^2+5x+2 \geq x^2+x\\
x^2+4x+2 \geq 0\\
D=16-4*1*2=8\\
x=\frac{-4+\sqrt{8}}{2}=-2+\sqrt{2}\\
" alt="
21x^2+39x-6<0\\
\frac{1}{x}+\frac{1}{x+1}>=\frac{1}{x+2}\\\\
21x^2+39x-6=0\\
7x^2+13x-2=0\\
D=13^2-4*7*-2=225\\
x=\frac{-13+15}{14}=\frac{1}{7}\\
x=\frac{-13-15}{14}=-2
(7x-1)(x+2)<0\\
x \ \in \ (-2;\frac{1}{7})\\\\
\frac{1}{x}+\frac{1}{x+1} \geq \frac{1}{x+2}\\
\frac{2x+1}{x(x+1)} \geq \frac{1}{x+2}\\
\frac{(2x+1)(x+2)}{x(x+1)(x+2)} \geq \frac{x(x+1)}{x(x+1)(x+2)}\\
(2x+1)(x+2) \geq x(x+1)\\
2x^2+5x+2 \geq x^2+x\\
x^2+4x+2 \geq 0\\
D=16-4*1*2=8\\
x=\frac{-4+\sqrt{8}}{2}=-2+\sqrt{2}\\
" align="absmiddle" class="latex-formula">
![x=\frac{-4-\sqrt{8}}{2}=-2-\sqrt{2}\\
x \in [-\sqrt{2}-2;-2)\ \cup \ (-1;\sqrt{2}-2] \ \cup \ (0;\infty) x=\frac{-4-\sqrt{8}}{2}=-2-\sqrt{2}\\
x \in [-\sqrt{2}-2;-2)\ \cup \ (-1;\sqrt{2}-2] \ \cup \ (0;\infty)](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-4-%5Csqrt%7B8%7D%7D%7B2%7D%3D-2-%5Csqrt%7B2%7D%5C%5C%0Ax+%5Cin+%5B-%5Csqrt%7B2%7D-2%3B-2%29%5C+%5Ccup+%5C+%28-1%3B%5Csqrt%7B2%7D-2%5D+%5C+%5Ccup+%5C+%280%3B%5Cinfty%29)
с учетом ОДЗ
Объединяя